Effects of Strain Node on the Actuation Performance of Multilayer Cantilevered Piezoactuator with Segmented Electrodes. (3rd March 2022) - Bai, Quan; Zheng, Xuejun
Abstract : A model of a segmented electrode multilayer cantilever piezoelectric actuator was established to predict its actuation performance, and then, theoretical and numerical analyses of the strain nodes were performed based on normalized deflection and strain distributions. The segmented electrodes instead of the continuous electrodes are applied in a multilayer cantilever piezoelectric actuator which can avoid the modal displacement offsets at the high vibration modes, thereby enhancing the tip deflection. The theoretical analysis and simulation results show that the tip deflection of the segmented electrode at the second mode was almost 100% larger than that of the continuous electrode. At the second mode, the maximum error between the theoretical calculation value of the tip deflection and the simulation result is 6.8%. It is because the segmented electrode is optimally designed at the strain node, which avoids the modal displacement offsets of a multilayer cantilever piezoelectric actuator at the high vibration modes; meanwhile, the theoretical results are closer to the FEM simulation results. It reveals that the tip deflection of a multilayer cantilever piezoelectric actuator can be precisely estimated by the proposed model. This research can provide some useful guidance improving the actuation performance and optimizing the design of a multilayer cantilever piezoelectric actuator.